Benefits of using Augmented Reality in education - Hasan o’g’li, Shokhrukhbek Rasulov; Sobir qizi, Mekhriniso Rasulova; Abdullayevich, Giyosiddin Safarov; Absamatovna, Gavhar Hamdamova; Oktyabrevna, Nargiza Rakhmatullayeva (International Journal of Psychosocial Rehabilitation, 2020)
Using augmented reality in education sphere is merely a news. However, specific benefits of use have not been studied thoroughly yet. Thus, implementation of augmented reality is being avoided by majority of institutions, which according to our conclusion, has to be worked on. The article demonstrates how augmented reality is applied in many spheres and is of great perspectives in field of education, specifically language teaching. The present work focuses on particular language skills of students, which might be enhanced using augmented reality in classroom.